A revegetation strategy based on the management of arbuscular mycorrhizae, Rhizobium and rhizobacterias for the reclamation of desertified Mediterranean shrubland ecosystems - Barea J.M.; Requena N.; Jiménez I. (La mycorhization des plantes forestières en milieu aride et semi-aride et la lutte contre la désertification dans le bassin méditerranéen, 1996)
A research programme is proposed for shrubland ecosystem recovery, i.e., to improve soil stabilization, and to restore a stable and diversified matorral in certain pilot-units representative of a Mediterranean desertified semi-arid ecosystem. The research approach is based on enhancing the colonization ability of woody legumes belonging to the natural succession. In this context, legumes are of special importance since they are able to take advantage of their ability to fix N2 in symbiosis with Rhizobium, and to form mycorrhizae. In this symbiosis the fungal partner colonizes and links root and surrounding soil to play a critical role by improving plant rooting and establishment, helping plants to cope with stress situations such as nutrient deficiencies, drought, contamination and soil disturbance. Plant Growth Promoting Rhizobacteria will be also applied. Because soil erosion reduces the number and activity of mycorrhizal propagules the restoration of the mycorrhizal potential could be a key factor to enhance the ecosystem recovery rate. It is proposed to follow parameters related to 'soil quality' (aggregate formation, organic matter, N, P levels, micronutrient equilibria, etc.), plant cover development (plant growth, nutrient acquisition, stress resistance, diversity, demography, etc.), system ability for 'self-mycorrhization', etc. Current methodological approaches will be applied, such as those for rhizosphere biotechnology (molecular biology, isoenzymatic profiles, etc.), isotopic techniques (15N, 32P, 13C), analytical methods in physiochemistry, ecophysiology, biometry, etc.
Séminaire du Groupe de Travail CIHEAM sur l'Utilisation des Mycorhizes pour la Lutte contre la Désertification dans le Bassin Méditerranéen (MYCOLUDESME), 1995/11/15-17, Zaragoza (Spain)